Fenomena Pernikahan Dini (Studi Kasus Fenomena Pernikahan Dini Desa Sudimara Kecamatan Tabanan Kabupaten Tabanan Antropologi Kesehatan) - Pasek Hartono, I Made (Humanis, 2016)
Health behaviors exhibited by individuals or specific groups have a lot of spotlight on lately . Adolescent reproductive health problems, especially early marriage phenomenon that often happens in Bali both in urban and rural are as is interesting to study because of early marriage can be a negative impact on their future life. In connection with the focus this research. Based on the method and the theory of this study found that the knowledge and attitudes of teenagers to wards early marriage Sudamara village is still lacking. Factors that lead to early marriage is a factor the lack of knowledge about adolescent reproductive health, family economic, social and cultural upbringin.
Keywords: Early Marriage, Reproductive Health, Health Behavior